2009
DOI: 10.3899/jrheum.080791
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing Surveillance of the Safety and Effectiveness of Etanercept in Japan

Abstract: Objective.Postmarketing surveillance (PMS) was conducted evaluating safety and effectiveness of etanercept (ETN; Enbrel®) in Japan, following all patients with rheumatoid arthritis (RA) during the conditional approval period of ETN.Methods.Registration of patients from 1,334 medical sites was conducted between March 2005 and April 2007. Patients were followed for 24 weeks; data regarding patients’ background, safety, and effectiveness was recorded centrally. Adverse events (AE) and adverse drug reactions (ADR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 16 publications
10
96
3
3
Order By: Relevance
“…Among the latter, six patients discontinued due to pneumonia. Pneumonia was the most frequent adverse event observed in previous Japanese post-marketing surveillance (PMS) evaluation of infliximab [40] and etanercept [27], which is consistent with the results of our study. However, it should be noted that susceptibility to infection is an important concern not only in association with anti-TNF therapies but also with the anti–IL-6 activity of tocilizumab.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the latter, six patients discontinued due to pneumonia. Pneumonia was the most frequent adverse event observed in previous Japanese post-marketing surveillance (PMS) evaluation of infliximab [40] and etanercept [27], which is consistent with the results of our study. However, it should be noted that susceptibility to infection is an important concern not only in association with anti-TNF therapies but also with the anti–IL-6 activity of tocilizumab.…”
Section: Discussionsupporting
confidence: 93%
“…Government regulations have limited the maximum dose of MTX to 8 mg/week in Japan; however, many rheumatologists prescribe higher MTX doses off-label [24, 27]. It is remarkable that such low-dose MTX potentiates tocilizumab action in severe RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression analysis identified the following risk factors for serious infection: age ≥ 65 years, longer disease duration (≥ 10 yrs), previous or concurrent respiratory disease, and mean concomitant corticosteroid dose > 5 mg/day (prednisolone equivalent). The risk factors for serious infection identified in our study are similar to the findings reported from the all-patient PMS conducted for infliximab, etanercept, and adalimumab in Japan 1,13,14,15 . Patients with 3 or more of these risk factors had a cumulative incidence of serious infection about 10 times that of patients with no risk factors.…”
Section: Rheumatologysupporting
confidence: 79%
“…In addition, we have found in the literature four cases of fatal pulmonary NTM infections that occurred during anti-TNFα therapy for rheumatic diseases [30–33]. Until now, however, no fatal case of NTM disease has been reported in the Japanese postmarketing surveillance of biological therapy for RA [3437]. In the present study, therapeutic responses to anti-NTM therapy were also favorable.…”
Section: Discussionsupporting
confidence: 65%